Narratology of fictional dreams in the Russian literary works - Aleksey A. Zaginaiko, Vera V. Savelyeva, Olga Y. Zaginaiko, Lyutsiya I. Abdullina, (Opción, 2019)
This article deals with studying fictional dreams and its representation in the world literature. The material of this study encompassed 80 fictional dreams taken from the Russian literary works. The models got the following working titles: perspective, bidirectional, dotted and the final model. Identifying the correlation of narratives gives the possibility to identify connections between the sleeping and the active consciousness of the character. Determination of narrative forms is based on identification of different viewpoints of the narrators during verbal construction of dreams. Narratives of fictional dreams can be regarded as a specific kind of psych narration